Acne: the clinical course and features of therapy - Z. Sh. Garaeva; L. A. Yusupovа; E. I. Yunusovа; G. I. Mavlyutova; D. E. Lukanina (Лечащий Врач)
The article highlights the information about the etiopathogenesis of acne, the features of the clinical course of various forms of the disease and possible treatments. The features of acne treatment in adolescents are considered in detail. The article describes the features of the treatment of late acne in women and combined therapy in acne patients of different levels of severity.